Successful parathyroidectomy improves cognition in patients with primary hyperparathyroidism: A prospective study in a tertiary medical center and comprehensive review of the literature - Szalat, Auryan; Tamir, Noa; Mazeh, Haggi; Newman, J. P. (Frontiers in Endocrinology, 2022)
Context - The recent American and European guidelines on management of patients with primary hyperparathyroidism (PHPT) did not endorse neurocognitive evaluation as part of standard work-up and did not consider it as a surgery criterion.The neurocognitive deleterious effects of hyperparathyroidism and impact of parathyroidectomy on PHPT patients is yet to be elucidated. Objective – To evaluate specific neurocognitive functions in PHPT patients prior to parathyroidectomy and describe the changes during follow-up with serial evaluations. Design - A prospective case-control study including parathyroidectomy candidates evaluated at a tertiary teaching university hospital. Thorough neurocognitive evaluation was conducted before and 1- & 6-months following parathyroidectomy: Rey Auditory Verbal Learning Test (RAVLT), Rey-Osterrieth Complex Figure Test (ROCF), Trail Making Test A, Trail Making Test B, Addenbrooke’s Cognitive Examination-III (ACE), Frontal Assessment Battery (FAB), Beck Depression Inventory (BDI). Results - 18 consecutive patients underwent successful parathyroidectomy. Various neurocognitive functions improved significantly after successful parathyroidectomy: long term auditory memory (RAVLT, p=0.008), short- and long-term visual memory (ROCF, p=0.006 and p=0.002 respectively), visual attention and complex concentration skills (trail making A, p<0.001) and executive abilities (trail making B, p=0.005). No change was identified in frontal-lobe abilities. Depression symptoms were absent or minimal prior to surgery and no significant change was observed after surgery. Conclusions – PHPT is associated with significant various neurocognitive dysfunctions when mindfully evaluated before surgery. Successful parathyroidectomy results in several neurocognitive aspect improvements. The data suggest that neurocognitive deterioration may be considered an added parathyroidectomy criterion when surgical decision is not straightforward.